Cambridge guide to mentalization-based treatment (MBT) - Bateman, Anthony 1952-; Fonagy, Peter 1952-; Campbell, Chloe; Luyten, Patrick; Debbané, Martin (Cambridge University Press, 2023)
"An up-to-date and practical guide to mentalization-based treatment (MBT) for clinicians and researchers, covering the latest developments in mentalizing and MBT, the interventions refined in clinical practice for a range of psychological disorders, and the use of mentalizing in various contexts, described with illustrative clinical examples"--
Includes bibliographical references and index
Keywords: Mentalization Based Therapy; Mentalization-Based Therapy